Congenital lobar emphysema: a rare cause of respiratory distress in a neonate - Mittal, Nishant; Parakh, Ankit; Jain, Prashant; Mittal, N. K. (International Journal of Contemporary Pediatrics, 2018)
Congenital lobar emphysema (CLE) is a congenital condition characterized by distension and air trapping of the affected lobe of the lung. It is one of the causes of infantile respiratory distress, which may require surgical resection of affected lobe. Case characteristics: 3-day-old neonate with ventilation refractory respiratory distress. Imaging was suggestive of decreased lung tissue on the right side with ipsilateral mediastinal shift. Intervention/ outcome: Early surgical lobectomy was done to improve lung functions and the child improved dur to early intervention. Message: An early diagnosis with high index of suspicion helps patients with this rare congenital anomaly. Early intervention is the key to good long-term outcome. More awareness about the entity and treatment options available would greatly help improving the outcome and disease burden.